Industrial workstations design: a real case study. (18th July 2012) - Cimino, Antonio; Mirabelli, Giovanni
This research work advances the effective design of the most critical workstations belonging to a real industrial plant. To this end, the authors propose an approach based on the integration of Modelling & Simulation (M&S) tools, several ergonomic standards and the best known work measurement tools. The effective design of the workstations is achieved by using the simulation model for comparing workstations' alternative configurations. The comparison is based on ergonomic and time indexes related to the ergonomic standards and the work measurement tools. Such comparison allows to choose the workstations' final configurations.